The Many Faces of Rural Capitalism. Issue 1 (26th February 2020) - Clark, Christopher
Abstract: The territorial growth and capitalist development of the United States that began in the late eighteenth century entailed ‐‐ among other things ‐‐ a massive expansion of agriculture that continued until the 1920s. Though based on private, freehold property in land there was no single pattern to this agrarian growth or to agriculture's integration into national and global flows of commodities, finance, and labor. Slave and non‐slave systems expanded in parallel until 1860, but even the destruction of slavery during the Civil War and the subsequent emergence of industrial and finance capitalism did not impose uniformity on American agriculture or undermine independent, household‐based farming.